2012
DOI: 10.2147/dmso.s23261
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological approaches to the management of type 2 diabetes in fasting adults during Ramadan

Abstract: More than 50 million Muslims throughout the world with type 2 diabetes mellitus (T2DM) fast for one lunar month (Ramadan) each year. Health care providers within and outside the Muslim world need to be aware of the nature of these partial days of fasting and their risks (and potential benefits) to people with T2DM, and need to provide Ramadan-adjusted diabetes care. Hypoglycemia during the fasting days represents the greatest health risk for these patients; hence, diabetes-related pharmacotherapy needs to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 36 publications
0
26
0
2
Order By: Relevance
“…In general, an adjustment of antidiabetic medications before Ramadan including marked dose reductions, and/or an increase in food/sugar intake when the fast is broken can underlie hyperglycemia during Ramadan. In addition, a long fasting period in the absence of adequate insulin can lead to excessive hepatic glycogen breakdown and increased gluconeogenesis, contributing to the development of hyperglycemia 4,6,7…”
Section: Introductionmentioning
confidence: 99%
“…In general, an adjustment of antidiabetic medications before Ramadan including marked dose reductions, and/or an increase in food/sugar intake when the fast is broken can underlie hyperglycemia during Ramadan. In addition, a long fasting period in the absence of adequate insulin can lead to excessive hepatic glycogen breakdown and increased gluconeogenesis, contributing to the development of hyperglycemia 4,6,7…”
Section: Introductionmentioning
confidence: 99%
“…Sixty-two percent of our patients had low education level. High illiteracy rate is barrier for providing the necessary Ramadan-focused diabetes education [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, a majority of Muslim patients with type 2 diabetes mellitus (T2DM) do not consider themselves ill, and are ardent about their Ramadan fasting, despite the complications such as hyperglycemia and hypoglycemia, diabetic ketoacidosis, dehydration, and thrombosis. 2,3 The Population-based Epidemiology of Diabetes and Ramadan (EPIDIAR)study showed that there was a 7.5-fold increase in the risk of severe hypoglycemic events (HEs)and a 5-fold increase in hospitalization due to hypoglycemia in fasting patients with T2DM. 4 Therefore, the risk of hypoglycemia is to be taken into account while choosing or maintaining an antidiabetic agent during Ramadan.…”
Section: Introductionmentioning
confidence: 99%